Pneumococcal Extracellular Serine Proteases: Molecular Analysis and Impact on Colonization and Disease - Ali, Murtadha Q.; Kohler, Thomas P.; Schulig, Lukas; Burchhardt, Gerhard; Hammerschmidt, Sven (Frontiers in Cellular and Infection Microbiology, 2021)
The pathobiont Streptococcus pneumoniae causes life-threatening diseases, including pneumonia, sepsis, meningitis, or non-invasive infections such as otitis media. Serine proteases are enzymes that have been emerged during evolution as one of the most abundant and functionally diverse group of proteins in eukaryotic and prokaryotic organisms. S. pneumoniae expresses up to four extracellular serine proteases belonging to the category of trypsin-like or subtilisin-like family proteins: HtrA, SFP, PrtA, and CbpG. These serine proteases have recently received increasing attention because of their immunogenicity and pivotal role in the interaction with host proteins. This review is summarizing and focusing on the molecular and functional analysis of pneumococcal serine proteases, thereby discussing their contribution to pathogenesis.